2005
DOI: 10.4103/0378-6323.18942
|View full text |Cite
|
Sign up to set email alerts
|

A study of autologous melanocyte transfer in treatment of stable vitiligo

Abstract: Autologous melanocyte transplantation can be an effective form of surgical treatment in stable but recalcitrant lesions of vitiligo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
63
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 7 publications
8
63
0
Order By: Relevance
“…As regards the sex of the patients in this study there were 13 females and 7 males and this study found no correlation to this item and the result of repigmentation, this is the same as what found by the Gauthier result, [11] Sobhy [12] and flabella [13]. In the present study, it was found that the site of the lesions did not significantly affect the result but the mean percentage of repigmentation of the treated area was greater in patients with skin lesions located in the face (89.67±11.76%) compared to those of the patients with skin lesions located in the neck (87.75±13.22%), and those located in the back (86.65±12.53%) and those lesions located in the chest (83.50±14.48%), this is different from the result of Pandya [14] study who found that in the fifty-one sites in 27 patients were chosen for autologous melanocytes transplantation, the most common sites were the feet (45.1%), legs (29.4%), hands (9.8%), knees (3.9%) and the face (3.9%), Pandya [14] results were most favorable on the legs, feet, face and the forearms, and poor on the elbows and the acral areas of the hand. Pandya [14] emphasis that the location of the recipient site was the major determinant of the outcome; acral parts including the dorsal aspects of the hands and feet, and the skin over the joints were less responsive, as 2 patients each with lesions on the hands and feet, and 1 patient with lesions on the elbow had a poor response, Pandya [14] said also that the fingers, the knuckles and the elbows were the most difficult areas to repigment, in part because of the relative uncertainty in controlling the depth of dermabrasion of such heavily cornified areas and also because of the high mobility of the skin covering these joints and so Pandya found also positive correlation with light exposed areas, this difference from the present study may be due to small case number and no acral cases and no cases with joint affection in the present study, but in accordance to Mulkar [15] who found poor response in the sun exposed areas and said that the sun may be a traumatic factor, but Sobhy [12] found that the exposed areas had better prognosis, these differences between the multiple studies may be due to the different degree of sun radiation on the earth and individual variation in melanocytic response to ultraviolet stimulation.…”
Section: Discussionmentioning
confidence: 58%
“…As regards the sex of the patients in this study there were 13 females and 7 males and this study found no correlation to this item and the result of repigmentation, this is the same as what found by the Gauthier result, [11] Sobhy [12] and flabella [13]. In the present study, it was found that the site of the lesions did not significantly affect the result but the mean percentage of repigmentation of the treated area was greater in patients with skin lesions located in the face (89.67±11.76%) compared to those of the patients with skin lesions located in the neck (87.75±13.22%), and those located in the back (86.65±12.53%) and those lesions located in the chest (83.50±14.48%), this is different from the result of Pandya [14] study who found that in the fifty-one sites in 27 patients were chosen for autologous melanocytes transplantation, the most common sites were the feet (45.1%), legs (29.4%), hands (9.8%), knees (3.9%) and the face (3.9%), Pandya [14] results were most favorable on the legs, feet, face and the forearms, and poor on the elbows and the acral areas of the hand. Pandya [14] emphasis that the location of the recipient site was the major determinant of the outcome; acral parts including the dorsal aspects of the hands and feet, and the skin over the joints were less responsive, as 2 patients each with lesions on the hands and feet, and 1 patient with lesions on the elbow had a poor response, Pandya [14] said also that the fingers, the knuckles and the elbows were the most difficult areas to repigment, in part because of the relative uncertainty in controlling the depth of dermabrasion of such heavily cornified areas and also because of the high mobility of the skin covering these joints and so Pandya found also positive correlation with light exposed areas, this difference from the present study may be due to small case number and no acral cases and no cases with joint affection in the present study, but in accordance to Mulkar [15] who found poor response in the sun exposed areas and said that the sun may be a traumatic factor, but Sobhy [12] found that the exposed areas had better prognosis, these differences between the multiple studies may be due to the different degree of sun radiation on the earth and individual variation in melanocytic response to ultraviolet stimulation.…”
Section: Discussionmentioning
confidence: 58%
“…As regards to the side effects they were mild and did not necessitate cessation of therapy, infection, erythema, itching, burning sensation, rigors and fever was the most common seen side effects. Some minor complications were also observed in Pandya et al [34]. Two (10%) patient shad infection at the donor area and one (5%) developed infection at the recipient surface.…”
Section: Discussionmentioning
confidence: 64%
“…The results of both studies revealed that the type of vitiligo is an important factor affecting the results of surgical procedures. In another study by Pandya et al [24] which included 27 patients they used autologous melanocyte rich cell suspension (uncultured), and cultured melanocytes suspension. Excellent response was seen in (50%) with the melanocyte culture (MC) technique and this result match with our study as excellent response was seen in (50%) of patients.…”
Section: Discussionmentioning
confidence: 99%
“…5,6,7 and the punch grafting technique. Both these techniques share a common principle of selective replenishment of pigment cell.…”
Section: Methodsmentioning
confidence: 99%
“…The supernatant was discarded and the pellet containing cells from the stratum basale. 7 and lower half of the stratum spinosum that were rich in melanocytes was taken. The pellet was resuspended in a total volume of 0.8ml DMEM medium and transferred gently in steps to a syringe.…”
Section: Laboratory Procedures For Cell Separationmentioning
confidence: 99%